A rare giant renal angiomyolipoma in a 17-year-old male: A case report - Fred Laizer; Hanson Nkini; Heri Babu; Erasto Medard; Amon Bamanyis; Teodros Veronesi (Urology Case Reports)
Renal angiomyolipoma is an uncommon benign tumor that mostly affects adults and is highly associated with tuberous sclerosis. It's very uncommon for it to affect adolescents. In this case, a 17-year-old male with abdominal pain and distension was diagnosed with sporadic giant renal angiomyolipoma. Histopathology confirmed the diagnosis after a successful nephrectomy. Though rare in teenagers, giant renal angiomyolipoma can be managed with surgery. Histopathology is a mainstay of confirming the diagnosis. Conclusion: This case highlights the difficulties in managing big retroperitoneal tumors in teenagers and the necessity of taking sporadic angiomyolipoma into account when making a differential diagnosis.